Nurse Navigation and the Transition to Cancer Survivorship: A Review of Determinants Essential to Program Success - Giunti, Amanda (Université d'Ottawa | University of Ottawa, 2013)
Nurse navigation programs are becoming prominent in the field of cancer care. As a newly emerging field, nurse navigation employs nurses and other health care professionals who assist patients in overcoming barriers throughout the cancer continuum. The concept of nurse navigation is being extended to focus on survivorship, which is described as the period following active cancer treatment where patients often encounter barriers affecting their care and quality of life. By utilizing specific skills and modalities, including education, communication, and coordination, survivorship navigators are able to assist in reducing disparities such as knowledge and communication inadequacies, thus, facilitating optimal access to survivorship care. Access to health services is an important determinant of health in Canada. Survivorship navigation programs incorporate health services, providing a method in which cancer patients can overcome challenges and improve their health outcomes. This review will discuss the origins of nurse navigation, highlight navigator skills and modalities, which are essential to program success, and finally discuss the implications of a survivorship navigation program.
Keywords: Survivorship nurse navigation; Cancer survivorship; Access to health care